Measuring Multidimensional Regional Disparity in Blitar Regency Using the Gini Index, Lorenz Curve, and Factor Analysis - Istiqmalah, Afina; Wicaksono, Agus Dwi; Nita, Inayah Widya; Apsari, Lindya (Perencanaan Wilayah dan Kota FT UB, 2026)
Regional disparity remains a critical development challenge in Blitar Regency, East Java, particularly between the relatively more developed northern area and the geographically constrained southern area. This study aims to measure the level of regional disparity across sub-districts and identify the dominant factors influencing the north–south development gap. A quantitative approach was applied using primary data from questionnaires distributed to relevant Regional Apparatus Work Units and secondary data from official statistical, planning, and sectoral documents. The Gini Index and Lorenz Curve were used to measure the distributional inequality of 18 physical, economic, social, infrastructure, accessibility, and geographical variables, while factor analysis was employed to identify the main dimensions of regional disparity. The results show that most variables have low to moderate inequality, but PDAM customers and damaged road conditions show high disparity, with Gini Index values of 0.78 and 0.60, respectively. These findings indicate that basic-service access and road quality are the most critical expressions of spatial inequality in Blitar Regency. Factor analysis identifies five dominant dimensions: regional economic potential, public facilities, accessibility and basic infrastructure, social conditions, and geographical conditions. Regional economic potential explains the largest variance, yet infrastructure inequality remains central because it affects the ability of peripheral sub-districts to access markets, public services, and development opportunities. The study concludes that disparity in Blitar Regency is multidimensional and requires targeted infrastructure investment, PDAM expansion, road rehabilitation, and spatially sensitive development planning.